Evaluative lexis in contemporary publicistic discourse: lexicological and psycholinguistic projection - Melnyk, Iryna; Masytska, Tetiana; Holoiukh, Larysa; Kravchuk, Volodymyr; Polezhaieva, Tetiana; Honchar, Kateryna (My University, 2022)
The article analyzed the evaluative markers used in the Ukrainian media discourse of the last decade according to their meaning, stylistic and psycholinguistic features. The influence of extra-linguistic factors on the dynamics of the analysed evaluative lexis was identified. The semantic specificity of evaluative lexical means, which were classified into semantic groups, was outlined. It was proved that evaluative lexis in mass-media discourse is primarily associated with the form of speech influence – manipulation, which presupposes changes in the person’s psychological features, group norms, and public opinion. Evaluative lexical means were characterized in relation to social-political and social-economic factors, which we associate with the actualization of the existing lexical means and appearance of new ones, mainly of negative evaluative connotation to name particular people, political groups, the reflection of different events, phenomena, processes of reality. The linguistic means that strengthen the cheerful emotional evaluative colour of modern mass-media texts were analysed separately. The extra-linguistic factors that led to the appearance of positive evaluative lexical means were emphasized. Communicative pragmatic specialization of the utterances with negative or positive evaluative lexical means was revealed. Context modifications of linguistic units with evaluative connotation and their manipulative influence on the participants of the communication process were studied. Derivative evaluative lexical means from the point of view of word combinations and sentences were characterized. Most of the analysed secondary nominations predict negative evaluation, produce negative emotions, contribute to text comprehension, informativeness with the help of verbal formulas, and graphic character reduction due to specific spelling.
Keywords: evaluative lexical markers; lexical means of positive evaluation; lexical means of negative evaluation; semantic groups; noun; verb; adjective; journalistic discourse; political discourse.